Life : learning interactively for engagement : meeting the pedagogical needs of students from refugee backgrounds : student modules : short intensive program. - Silburn, Jenny; Earnest, Jaya; De Mori, Gabriella; Butcher, Linda (Australian Learning and Teaching Council (ALTC), 2010)
The Murdoch and Curtin University design teams designed, developed and trialled teaching and learning modules that addressed the academic needs of students identified in the needs analysis stage of the Life project. The learning and teaching modules were trialled with a cohort of students from refugee backgrounds at each university in Semester 1, 2009. These modules have been developed in response to identified needs of students from refugee backgrounds. The following modules were delivered in semester 1, 2009. The modules can be modified in response to student feedback at different universities and can be used in different contexts.